ANALISIS PENGARUH UKURAN PERUSAHAAN, LIKUIDITAS DAN LEVERAGE TERHADAP PENERIMAAN OPINI AUDIT GOING CONCERN - Yesi Kusumaningrum; Zulaikha Zulaikha (Diponegoro Journal of Accounting, 2019)
This study aims to examine the relationship between firm size, likuidity ratio, leverage ratio to going concern opinion. The independent variables used in this study are firm size, likuidity and leverage while the dependent variable is going concern opinion.The samples used area a manufacturing companies listed on the Indonesia Stock Exchange in 2016 and 2017. The sampling technique is purposive sampling method, 99 companies have met the predetermined sample criteria. This study uses logistic regression to examine hypothesis. The results indicate likuidity rasio have significant effect to going concern. On other hand firm size and leverage rasio not have significant effect to going concern opinion.